2002
DOI: 10.1097/00002060-200211001-00016
|View full text |Cite
|
Sign up to set email alerts
|

Adaptations to Exercise Training and Contraction-Induced Muscle Injury in Animal Models of Muscular Dystrophy

Abstract: This article reviews the current status of exercise training and contraction-induced muscle-injury investigations in animal models of muscular dystrophy. Most exercise-training studies have compared the adaptations of normal and dystrophic muscles with exercise. Adaptation of diseased muscle to exercise occurs at many levels, starting with the extracellular matrix, but also involves cytoskeletal architecture, muscle contractility, repair mechanisms, and gene regulation. The majority of exercise-injury investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0
5

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 64 publications
3
39
0
5
Order By: Relevance
“…For many patients with muscular dystrophy, an increase in formal physical activity may not always be possible; however, several studies have demonstrated the feasibility and efficacy of moderate-strength exercise-training in patients with muscular dystrophy 5,25 and in animal studies. 4,49 Future studies combining a modified resistance exercise program with CrM supplementation will likely have the best chance of demonstrating significant increases in strength, fat-free mass, and function in patients with muscular dystrophy.…”
Section: Discussionmentioning
confidence: 99%
“…For many patients with muscular dystrophy, an increase in formal physical activity may not always be possible; however, several studies have demonstrated the feasibility and efficacy of moderate-strength exercise-training in patients with muscular dystrophy 5,25 and in animal studies. 4,49 Future studies combining a modified resistance exercise program with CrM supplementation will likely have the best chance of demonstrating significant increases in strength, fat-free mass, and function in patients with muscular dystrophy.…”
Section: Discussionmentioning
confidence: 99%
“…90,91 Studies using animal models of muscular dystrophy have shown that high-intensity eccentric contractions may indeed have deleterious effects on muscle integrity, especially in older muscles with limited capacity for regeneration. 92 Whereas the use of light resistance training consisting primarily of concentric actions may bring about some benefits, eccentric training does not seem to be appropriate to restore muscle function in these patients.…”
Section: Myopathic Diseasesmentioning
confidence: 99%
“…The main objective of such motor physical therapy is the prevention of muscle contractures and bone deformities (Strober, 2006). However, motor PT approaches have yielded controversial recommendations (Carter et al, 2002) and there is no consensus regarding the type and intensity of PT (Cup et al, 2007). Just as other muscular dystrophies, DMD is a progressive disorder which causes death by cardiac or respiratory failure.…”
Section: Introductionmentioning
confidence: 99%